2010
DOI: 10.1111/j.1365-2915.2010.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval habitats and seasonal abundance of Culicoides biting midges found in association with sheep in northern Sardinia, Italy

Abstract: Abstract. Between January 2005 and December 2006, the larval habitats and seasonal abundances of 21 species of Culicoides (Diptera: Ceratopogonidae) found in association with livestock on a farm in northern Sardinia were studied. Culicoides were collected using two light traps (one placed in a sheep shed and the other near water ponds) and reared from mud collected in and along the margins of a small and a large water pond. The mammalophilic Culicoides imicola Kieffer and Culicoides newsteadi Austen were the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 22 publications
6
62
0
1
Order By: Relevance
“…Whereas males are not blood feeders and usually die after mating. Similar, sex wise prevalence pattern were also reported by Satheesha et al (2006), Reddy and Hafeez (2008), Deniz et al (2010), Foxi and Delrio (2010) and Kim et al (2012). During this study, 10 different Culicoides spp.…”
Section: Resultssupporting
confidence: 71%
“…Whereas males are not blood feeders and usually die after mating. Similar, sex wise prevalence pattern were also reported by Satheesha et al (2006), Reddy and Hafeez (2008), Deniz et al (2010), Foxi and Delrio (2010) and Kim et al (2012). During this study, 10 different Culicoides spp.…”
Section: Resultssupporting
confidence: 71%
“…Most species of the genus Culicoides are known to be either mammalophilic (Hair and Turner, 1968;Foxi and Delrio, 2010;Garros et al, 2011;Calvo et al, 2012) or ornithophilic (Bennett, 1960;Hair and Turner, 1968;Garvin and Greiner, 2003;Mullens et al, 2006; Martinez-de la Puente et al, 2009;Votypka et al, 2009;Foxi and Delrio, 2010;Cerny et al, 2011), although some feed on reptiles or frogs. In a previous study using animal-baited traps, horses were found to be the most attractive hosts for the three main Palaearctic Culicoides species, including C. obsoletus (Viennet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Culicoides abundance was found to decrease with increasing distance to potential hosts or breeding sites (Kettle, 1995;Lühken and Kiel, 2012;Kirkeby et al, 2013a). Moreover, it has been proposed that the direct surroundings of farms provide a huge number of potential breeding sites (Zimmer et al, 2008(Zimmer et al, , 2014Foxi and Delrio, 2010;González et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have increased our knowledge on the breeding sites and their colonisation by different Culicoides species (Foxi and Delrio, 2010;González et al, 2013;Harrup et al, 2013;Zimmer et al, 2014), the causal connections with environmental parameters mostly remain unknown. Therefore, besides the evaluation of different modelling techniques and the implementation of further environmental parameters, there is an urgent need for experimental studies on these relationships.…”
Section: Discussionmentioning
confidence: 99%